Killing the Father: 'Cultural Fathers' and Paternal Influence in Hibernian Philhellenism - McGurk, Sophie (Trinity College Dublin. School of Histories & Humanities. Discipline of Classics, 2026)
This thesis explores how certain tensions present in what W.B. Stanford previously termed the `Irish Classical Tradition' manifested in the lives, works, and relationships of several prominent figures in Irish literary culture from the late nineteenth century to the present. In order to demonstrate the effects of this cultural milieu, I consider three principal (male) figures against the critical theme of `cultural paternal influence', but inevitably other major `cultural fathers' are drawn into the discussion. My central focus is Oscar Wilde and I examine Wilde's direct and indirect relation to two further key characters: J.P. Mahaffy and Colm Tóibín. In order to contextualise this examination, Chapter 1 first re-defines and re-conceptualises a tradition of classicism in Ireland to show how it is neither hierarchal nor linear, but rather a complex cultural mosaic wherein each member is an active constructor of the tradition responding to their own fictive position within the same tradition. This chapter provides the architecture for the thesis' overarching argument which offers a new way of understanding classical Greek engagement in Ireland through the concept of `Hibernian Philhellenism' imagined as akin to Tim Ingold's `rope'. The idea that `the rejection of influence is still influence' is paramount. Chapter 2, therefore, establishes an agonistic exchange of influence between Wilde, Mahaffy and Tóibín framed by the patriarchal and parricidal nature of Greek tragedy. Since this thesis also places an understanding of the `author as reader' at the forefront, Chapter 3 interrogates the lived experiences of my predominant figures through their interaction with Platonic conceptions of homosocial and homoerotic relationships. Overall, this thesis does two things. Firstly, it establishes a new way in which a history of classicism in Ireland can be mapped, concluding that the current model rests somewhere `in between' theories of `tradition' and `reception'. Secondly, it illustrates what this approach may look like in practice by providing a thematic exploration of my selected figures across a number of chosen domains.
APPROVED
Keywords: Oscar Wilde; Colm Tibn; J. P. Mahaffy; Irish Classical Tradition; Irish Classical Reception; Trinity College Dublin; Irish Classicism; Tim Ingold; Harold Bloom; Literary Influence; Cultural Paternal Influence; The Anxiety of Influence; Intertextuality; The Author as Reader; Classical Greece; Classical Athens